Learning from near misses: from quick fixes to closing off the Swiss-cheese holes. Issue 4 (22nd February 2012) - Jeffs, Lianne; Berta, Whitney; Lingard, Lorelei; Baker, G Ross
Abstract : Introduction: The extent to which individuals in healthcare use near misses as learning opportunities remains poorly understood. Thus, an exploratory study was conducted to gain insight into the nature of, and contributing factors to, organisational learning from near misses in clinical practice. Methods: A constructivist grounded theory approach was employed which included semi-structured interviews with 24 participants (16 clinicians and 8 administrators) from a large teaching hospital in Canada. Results: This study revealed three scenarios for the responses to near misses, the most common involved 'doing a quick fix' where clinicians recognised and corrected an error with no further action. The second scenario consisted of reporting near misses but not hearing back from management, which some participants characterised as 'going into a black hole'. The third scenario was 'closing off the Swiss-cheese holes', in which a reported near miss generated corrective action at an organisational level. Explanations for 'doing a quick fix' included the pervasiveness of near misses that cause no harm and fear associated with reporting the near miss. 'Going into a black hole' reflected managers' focus on operational duties and events that harmed patients. 'Closing off the Swiss-cheese holes' occurred when managers perceived substantial potential for harm and preventability. Where learning was perceived to occur, leaders played a pivotal role in encouraging near-miss reporting. Conclusion: To optimise learning, organisations will need to determine which near misses are appropriate to be responded to as 'quick fixes' and which ones require further action at the unit and corporate levels.